STUDI TIPOLOGI RUMAH MASYARAKAT KALANGAN MENENGAH KE BAWAH DI SEMARANG: STUDI KASUS KAMPUNG JURNATAN, WONOSARI, DAN PATEMON - Novitasari, Ardia; Ana Hardiana,; Ofita Purwani, (Nature: National Academic Journal of Architecture, 2023)
Low-income settlements in Semarang City have become an issue in many cities, including Semarang City. This issue is caused by settlements that are formed organically in prohibited areas. This paper aims to find the applied typology by finding specific types that persist or recur in low-income settlements in Semarang. The typology can be used to design low-income mass housing in the city. This study used a qualitative and purposive sampling methods for the selected samples. A field study was conducted in three kampongs in Semarang with varying topographical conditions, specifically in Kampong Jurnatan (0-2% land slope), Kampong Wonosari (15-40% and>40% land slope), and Kampong Patemon (2-15% land slope). The results show several main characteristics of low-income housing in Semarang, including multifunctional rooms, rooms or areas for storage in every hsouse and communal spaces, and linear circulatory spaces that are also multifunctional for socializing in the Kampong area. These findings can be implied in the design criteria for horizontal and vertical low-income settlements.